2019
DOI: 10.1002/lary.28100
|View full text |Cite
|
Sign up to set email alerts
|

The endoscopic endonasal approach for sinonasal and nasopharyngeal adenoid cystic carcinoma

Abstract: Objective: To determine factors affecting outcomes for patients with sinonasal and nasopharyngeal adenoid cystic carcinoma (SNACC) treated using the endoscopic endonasal approach (EEA) with preservation of key structures followed by adjuvant radiotherapy (RT).Method: Retrospective case series of 30 patients treated at the University of Pittsburgh between 2000 and 2014. Hospital records were reviewed for clinical and pathologic data. Outcome measures included overall survival (OS), disease-free survival (DFS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Another study from the US found improved OS only for END performed in T3-T4 major salivary glands ACC; in this large dataset of over 2800 patients, the sinonasal cavity represented the second anatomical subsite in terms of frequency, but it was also the least likely to receive END and to harbor occult metastases [ 46 ]. Finally, in a recently published series of exclusively sinonasal ACC treated by endoscopic endonasal approaches, nodal recurrence occurred in only 1 out of 30 cases, and it was concomitant to distant metastases; again, adjuvant RT was delivered in 83% of patients but the fields were not specified [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study from the US found improved OS only for END performed in T3-T4 major salivary glands ACC; in this large dataset of over 2800 patients, the sinonasal cavity represented the second anatomical subsite in terms of frequency, but it was also the least likely to receive END and to harbor occult metastases [ 46 ]. Finally, in a recently published series of exclusively sinonasal ACC treated by endoscopic endonasal approaches, nodal recurrence occurred in only 1 out of 30 cases, and it was concomitant to distant metastases; again, adjuvant RT was delivered in 83% of patients but the fields were not specified [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two series report the results of 30 and 34 patients treated endoscopically. They report overall survival rates at 5 years of 62.7% and 86.5% and confirm that endoscopy is a valid surgical treatment modality [99,104]. Surprisingly, the study by Kashwazaki et al, which also included patients with adenoid cystic carcinoma of the nasopharynx, reported a clear surgical margin rate of 7% [104] which may seem too low to recommend this surgical strategy.…”
Section: Adenoid Cystic Carcinomamentioning
confidence: 94%
“…They report overall survival rates at 5 years of 62.7% and 86.5% and confirm that endoscopy is a valid surgical treatment modality [99,104]. Surprisingly, the study by Kashwazaki et al, which also included patients with adenoid cystic carcinoma of the nasopharynx, reported a clear surgical margin rate of 7% [104] which may seem too low to recommend this surgical strategy. However, the study by Volpi et al which reported a clear margin rate of 79.4% is in favor of the endoscopic approach with satisfactory carcinological results [99].…”
Section: Adenoid Cystic Carcinomamentioning
confidence: 94%
See 1 more Smart Citation
“…The role of postoperative radiotherapy in cases of stage T2 tumors is unclear, while some studies show no benefit, others show higher recurrence rates in the absence of radiotherapy, especially in cases of high-risk tumors, such as adenoid cystic carcinoma and undifferentiated carcinoma ( 108 111 ). In cases of squamous cell carcinoma with macroscopic or microscopic tumors after surgical treatment, concomitant hypoxic modification with the radiosensitizer nimorazol should be used ( 112 ).…”
Section: Postoperative Therapymentioning
confidence: 99%